KEPUTUSAN PEMBELIAN E-COMMERCE SHOPEE DITINJAU DARI WEBSITE QUALITY, INOVASI PRODUK, DAN ELECTRONIC WORD OF MOUTH (STUDI PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ISLAM BATIK SURAKARTA) - Tulus Dwi Prasetyo; Istiatin Istiatin; Bambang Mursito (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this research is to find out whether there is a significant influence between variable website quality, product innovation, and electronic word of mouth on e-commerce shopee purchasing decisions. In addition, it is also to find out whether there is a significant simultaneous effect and which variable is the most dominant in influencing the purchase decision of e-commerce shopee at the Faculty of Economics, Batik Islamic University, Surakarta. The method used is quantitative descriptive method. The population in this study amounted to 1330 students and the number of samples used was 133, where the sampling technique used quota sampling. The data used are primary data and secondary data with data collection techniques: observation, documentation, questionnaire and literature study. Data analysis techniques in this study used multiple linear tests. The results of the study can be concluded that: The results of the study can be concluded that: 1) There is the influence of website quality, product innovation, and electronic word of mouth simultaneously influence the purchasing decision of e-commerce shopee on the Students of the Faculty of Economics, Islamic University of Batik Surakarta, 2) There is an influence website quality on e-commerce shopee purchasing decisions at the Batik Faculty Islamic University Economics Faculty Students, 3) There is an influence on product innovation on e-commerce shopee purchasing decisions at the Batik Faculty Islamic Economics Faculty Students, 4) There is the influence of electronic word of mouth on the decision purchasing e-commerce shopee at the Faculty of Economics, Surakarta Islamic Batik University. Keywords: Purchasing Decisions, Website Quality, Product Innovation, Electronic Word Of Mouth